Promotional information system development based tourism in The Sinai - Merauke area religious, cultural and natural - Manggala, Fajar Wira Cakra; Sofyan, Fauzi; Ahmad, Umar Ali; Septiawan, Reza Rendian; Diana, Firmansyah; Purnamasari, Indah; Xaverius, Fransiskus; Budiasto, Jarot; Raubaba, Henry Soleman; Sumbung, Frederik H (Universitas Telkom, 2025)
Tourism is an industry that plays an important role in a country''s economy. Tourism offers a variety of cultural, natural and scenic experiences that enhance knowledge and understanding of the world. In an effort to improve tourism promotion in the village, especially in Kawasan Sinai, the development of a tourism information system is a very important research focus. In the implementation section of this system, the system implementation process will be explained from all parts of the sub-system that have been planned previously. The documentation listed is the current documentation for Kawasan Sinai -Merauke Area Tourism Information System Based on Religion, Culture, and Nature Tourism. The results of all testing methods show a 100% success rate, in accordance with website development planning. Thus, it can be concluded that the tourism promotion information system for visitors on Kawasan Sinai website has met the feasibility standards to be implemented and is ready to be used by users.The success of this project had a positive impact in enhancing the reputation of the sinal region as a promotional destination, as well as providing a smooth and satisfying user experience.